The dark tower : tales from the past - Vansittart, Peter; Gill, Margery (New York : Thomas Y. Crowell, 1969)
Eleven tales of Celtic origin interspersed with traditional poems and ballads tell of deeds of courage and treachery, magical powers, elf folk, and gods
Keywords: Folklore